Rentabilidad económica de la Empresa Prindex S.A del cantón Puebloviejo durante el periodo 2022 – 2023. - Pacheco Parra, Kelly Elizabeth (2025)
This research focuses on the economic profitability of the company Prindex S.A. in the Puebloviejo canton during the period 2022-2023. In recent years, Prindex S.A., dedicated to the cultivation of bananas and plantains, has faced significant economic challenges. These challenges include fluctuations in profit margins and increased expenses, which affect its liquidity and financial stability. The study analyzes the company's financial statements, using vertical and horizontal analysis to identify the causes of variations in profitability and liquidity. The objective of the research is to evaluate the economic performance of Prindex S.A., apply financial indicators and determine internal and external factors that affect profitability. An interview was conducted with the legal representative of the company and an internal control questionnaire was conducted to complement the financial analysis. The results show that, during the period 2022-2023, the company experienced a decrease in current assets and an increase in current liabilities, indicating a lack of liquidity. Furthermore, the company's profitability was affected by increased costs and expenses, and inadequate financial planning. The need to improve financial management and strategic planning is highlighted to face economic challenges and ensure long-term viability. It is recommended to implement measures to increase liquidity, optimize asset control and improve financial management practices. This includes reviewing cash flow, analyzing costs and looking for opportunities to reduce expenses without affecting product quality.